Investigating relationships among coping, personal growth, and life satisfaction among individuals with physical disabilities - Junhyoung Kim; Areum Han; Jennifer Ann Piatt; Jaehyun Kim (Tabriz University of Medical Sciences, 2020)
Background: It is well-documented that active coping strategies can lead to better positive adjustment and psycho-social outcomes among individuals with disabilities and illnesses. However, little information exists related to exploring how coping is related to health benefits such as personal growth and life satisfaction in an international context. Thus, this study examined how the use of coping strategies is associated with personal growth and life satisfaction among individuals with physical disabilities in non-Western settings. Methods: In this cross-sectional study, we employed a nonprobability methodology, purposivesampling, to recruit 351 participants who adults over the age of 18 living with a physicaldisability and currently enrolled in the Korean Disability Association. A hierarchical linearregression analysis was conducted to determine which types of coping strategies predictedpersonal growth and life satisfaction, while controlling for the effects of the demographicvariables (i.e., gender and age). Results: With regard to personal growth, problem-solving coping strategy (β = 0.663, P < 0.001,95% CI [0.51, 0.70]) was the strongest predictor, followed by avoidance coping strategy(β = -0.263, P < 0.001, 95% CI [-0.37, -0.20]). As for life satisfaction, problem-solving copingstrategy (β = 0.268, P < 0.001, 95% CI [0.18, 0.70]) was the strongest predictor, followed bysocial support seeking coping strategy (β = 0.264, P < 0.001, 95% CI [-0.19, 0.10]). Conclusion: Our study suggests that problem-focused and social support coping strategies playimportant roles in improving the personal growth and life satisfaction among Korean individualswith physical disabilities. This study provides implications for health professionals seeking waysto facilitate the personal growth and enhance the life satisfaction of individuals with physicaldisabilities.